Cryoconcentration technology applied in grape-based beverages: A review - Campos , Fábio Martins; Keiber , Morgana; Souto , Valter Oliveira de; Oliveira, Juliane Barreto de; Oliveira, Celso Guarani Ruiz de; Pereira , Giuliano Elias; Lazzarotto , Marcelo (Seven Editora, 2023)
This brief literature review aims to analyze relevant studies on the application of the cryoconcentration process in wine and grape juice. The cryo concentration consists of a non-thermal process of concentration of juices and wines capable of preserving most of the chemical, nutritional, functional, and sensory characteristics of the products, resulting in concentrated extracts of high quality and water with great purity. DOI:https://doi.org/10.56238/alookdevelopv1-032